1983
DOI: 10.1159/000145736
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Alkaline Phosphatase and NADH Diaphorase in the Principal Cells of the Guinea Pig Epididymis

Abstract: The activities of alkaline phosphatase and reduced nicotinamide adenine dinucleotide (NADH) diaphorase in the principal cells of the guinea pig epididymis were studied histochemically. Alkaline phosphatase activity was absent from the principal cells but was present in the basement membrane of the epididymal epithelium. NADH diaphorase activity was distributed throughout the cytoplasm of the principal cells in each epididymal segment. There was a gradual increase in NADH diaphorase activity from segments 1 thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
4

Year Published

1989
1989
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
4
0
4
Order By: Relevance
“…It is suggested that NADH + H + may be one of the reducing factors that play a role in the reduction of resazurin dye. This hypothesis is supported by the fact that NADH diaphorase activity has, indeed, been detected in spermatozoa ( Caldwell, 1976; Adams, 1983; Atanassov et al ., 1987 ; Gavella et al ., 1995 ), and that this enzyme was found to be highly expressed in the sperm midpiece ( Gomez et al ., 1996 ). In the resazurin reaction, the diaphorase enzyme transfers electrons from NADH + H + to the resazurin dye (blue) which becomes reduced to resorufin (pink). )…”
Section: Discussionmentioning
confidence: 78%
“…It is suggested that NADH + H + may be one of the reducing factors that play a role in the reduction of resazurin dye. This hypothesis is supported by the fact that NADH diaphorase activity has, indeed, been detected in spermatozoa ( Caldwell, 1976; Adams, 1983; Atanassov et al ., 1987 ; Gavella et al ., 1995 ), and that this enzyme was found to be highly expressed in the sperm midpiece ( Gomez et al ., 1996 ). In the resazurin reaction, the diaphorase enzyme transfers electrons from NADH + H + to the resazurin dye (blue) which becomes reduced to resorufin (pink). )…”
Section: Discussionmentioning
confidence: 78%
“…Foi observada principalmente na porção apical do epitélio de revestimento tubular, englobando o citoplasma supranuclear e apical das células P e apicais 15 . Estas observações são, até certo ponto, similares àquelas caracterizadas no epidídimo de algumas outras espécies de mamíferos, embora no rato e no cobaio as células P não mostraram reatividades para esta enzima 3,4 . Por outro lado, à semelhança das observações anteriores, feitas no rato e em outros mamíferos 4 e no cobaio 3 , a membrana basal tubular epididimária do gerbilo mostrou reatividade predominantemente forte à FoAl, cujo significado histofisiológico é a mediação enzimática que a FoAl exerce entre as células epiteliais e os capilares do estroma peritubular, no transporte de açúcares e outras moléculas orgânicas 3 .…”
Section: Discussionunclassified
“…Assim sendo, a FoAl reagia positivamente na borda microvilosa (de estereocílios) de todo o epidídimo, enquanto que a FoAc reagia fortemente nos dois segmentos epididimários proximais, localizados na cabeça epididimal de alguns mamíferos, como o coelho, cavalo, touro e carneiro 1,2 . Estes resultados foram similares às descrições feitas no epidídimo de outros mamíferos, destacando-se os roedores laboratoriais 3,4 .…”
Section: Introductionunclassified
See 2 more Smart Citations